Quantitative Proteomics and Transcriptomics Addressing the Estrogen Receptor Subtype-mediated Effects in T47D Breast Cancer Cells Exposed to the Phytoestrogen Genistein - Sotoca, Ana M. (The American Society for Biochemistry and Molecular Biology, 2011)
The present study addresses, by transcriptomics and quantitative stable isotope labeling by amino acids in cell culture (SILAC)-based proteomics, the estrogen receptor α (ERα) and β (ERβ)-mediated effects on gene and protein expression in T47D breast cancer cells exposed to the phytoestrogen genistein. Using the T47D human breast cancer cell line with tetracycline-dependent ERβ expression (T47D-ERβ), the effect of a varying intracellular ERα/ERβ ratio on genistein-induced gene and protein expression was characterized. Results obtained reveal that in ERα-expressing T47D-ERβ cells with inhibited ERβ expression genistein induces transcriptomics and proteomics signatures pointing at rapid cell growth and migration by dynamic activation of cytoskeleton remodeling. The data reveal an interplay between integrins, focal adhesion kinase, CDC42, and actin cytoskeleton signaling cascades, occurring upon genistein treatment, in the T47D-ERβ breast cancer cells with low levels of ERα and no expression of ERβ. In addition, data from our study indicate that ERβ-mediated gene and protein expression counteracts ERα-mediated effects because in T47D-ERβ cells expressing ERβ and exposed to genistein transcriptomics and proteomics signatures pointing at a clear down-regulation of cell growth and induction of cell cycle arrest and apoptosis were demonstrated. These results suggest that ERβ decreases cell motility and metastatic potential as well as cell survival of the breast cancer cell line. It is concluded that the effects of genistein on proteomics and transcriptomics end points in the T47D-ERβ cell model are comparable with those reported previously for estradiol with the ultimate estrogenic effect being dependent on the relative affinity for both receptors and on the receptor phenotype (ERα/ERβ ratio) in the cells or tissue of interest.